Students’ Perceptions of Using Group Work in Learning English in Nepal - Bhandari, Bhim Lal (Annual Oxford Journal, 2025)
Group work is regarded as an effective learner-centred technique and communicative method which encourages cooperative learning and engages students actively in the learning process. This study aims to discover secondary school students’ perceptions of using group work in learning English in Nepal. A quantitative descriptive survey research design was employed to carry out the study. Eighty respondents studying in grade 12 were randomly selected from four public schools in Rupandehi, Nepal. Two sets of closed-ended questions with a five-point Likert scale comprising 20 items were used as the primary tools for data collection. The findings revealed that most students had positive perceptions of using group work and valued it as a learner-centred methodology. Group work improves teamwork, communicative competence, and learner engagement in the learning process. However, uneven involvement, excessive mother tongue use, and less instructor supervision were some challenges in using it. Thus, this study can contribute to the transformation of the lecture method with the effective application of group work, increasing learners’ engagement in overall success of learning English.